ARTASHES TER-KHACHATURYAN: CONNOISSEUR ANDPUBLICIST OF DIASPORA PERIODICALS (Bulletin of Armenian Libraries, 2023)
The presentation examines Artashes Ter-Khachaturyan’sstudies devoted to Armenian periodicals from the core of his historical-philological research heritage.Over the years, he collected samples of the periodicals publishedin different colonies of the Armenian diaspora, not onlystudying and making them valuable publications, but alsoorganizing exhibitions in different parts of the world, promotingand making known this important part of national printingheritage.